The Role of Artificial Insemination in Successful Pregnancy of Cows in Lawe Loning Aman Village, Lawe Sigala-Gala District, Southeast Aceh Regency - Hadirin, Hadirin; Joharsah, Joharsah; Arwinsyah, Arwinsyah; Syaputra, Muhammad Ary; Sahpitri, Seroja; Fajar, Warpani; Assauwab, Muhammad Husaini (Fakultas Pertanian Universitas Muara Bungo, 2023)
This research investigates the role of artificial insemination (AI) on the successful pregnancy of cows in Lawe Loning Aman Village, Lawe Sigala-Gala District, Aceh Regency, which is effective in increasing livestock productivity by allowing control of the timing and quality of reproduction and reducing the risk of disease associa ted with natural mating. The results showed that the highest pregnancy rate (80%) occurred when insemination was carried out within 6-12 hours after the onset of oestrus, while the pregnancy rate decreased to 60% and 40% when insemination was carried out after 12-18 hours and more than 18 hours after the onset of heat. lust, respectively. These findings emphasize the importance of appropriate timing in implementing AI to increase the reproductive success of cows. In conclusion, this research provides important insights for livestock practitioners to consider the optimal time for implementing AI to increase livestock productivity effectively and sustainably in Lawe Loning Aman Village.